Ensiklopedia Burung Hias Indonesia Berbasis Multimedia - Murtadho, Hasan Faris; , Husni Thamrin, S.T, M.T, Ph.D (2016)
Encyclopedia is a book that contain information or explanation about various cases in the knowledge it is arranged in the alphabet way or based the knowledge area. In the informasion era nowdays technology progesses very fast. In the case can be looked at with there are new innovations that are able to created. So this research has aim to plan an application of the bird introducing in Indonesia by using macromedia flash 8. Creation of this application has aim to introduce the birds are in Indonesia. Application is made by some steps, started from looking for the bird data, design, create application, application is running well, finishing and burning into CD. Result of this application is made created in the CD from to using it. From the test result can be cocluded that the created program continue suitable the planning aim Keywords : Encyclopedia, CD (Compact Disc)